Systemic bioavailability, safety and tolerability of topical ozenoxacin in healthy adult volunteers. (August 2014) - Gropper, Savion; Albareda, Nuria; Santos, Benjamin; Febbraro, Salvatore
ABSTRACT: : A series of Phase I studies was conducted in healthy volunteers to examine the systemic bioavailability and safety of topical ozenoxacin. Study 1 examined increasing single doses (relating to quantity and body surface area) of ozenoxacin 1% ointment. Study 2 compared multiple doses of ozenoxacin 1% ointment and placebo applied for 7 days. Study 3 investigated multiple doses of ozenoxacin 2% cream and placebo applied for 7 days. Study 4 examined multiple doses of ozenoxacin 2% cream applied to intact and abraded skin for 8 days. No systemic absorption was observed in any study and ozenoxacin was well tolerated. The most common treatment-related adverse events were application-site reactions (erythema and pruritus), but the differences in local tolerability between ozenoxacin and placebo were not clinically significant.